2018
DOI: 10.1007/s40120-018-0121-0
|View full text |Cite
|
Sign up to set email alerts
|

A Videogame-Based Digital Therapeutic to Improve Processing Speed in People with Multiple Sclerosis: A Feasibility Study

Abstract: Introduction Self-administered in-home digital therapeutics could expand access to cognitive rehabilitation for individuals with multiple sclerosis (MS), over half of whom experience cognitive impairment (CI). However, feasibility in an MS population must be clarified. This study was conducted to assess the feasibility of deploying a videogame-like digital treatment for CI in MS, including initial efficacy and barriers to adherence. Methods In this pilot study, 21 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Previously, we showed that EVO-AKL-T01, a video game–based digital tool similar to EVO Monitor, is an effective in-home cognitive remediation program for MS [ 17 , 18 ]. The high adherence rate during the 4- to 6-week home-based cognitive rehabilitation strategy indicated that remote digital tools are well accepted by patients with MS, who may have limited access to cognitive assessment or treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we showed that EVO-AKL-T01, a video game–based digital tool similar to EVO Monitor, is an effective in-home cognitive remediation program for MS [ 17 , 18 ]. The high adherence rate during the 4- to 6-week home-based cognitive rehabilitation strategy indicated that remote digital tools are well accepted by patients with MS, who may have limited access to cognitive assessment or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A group of 24 adults without MS (non-MS) (mean age: 46.0, SEM 3.72 years) with no chronic autoimmune diseases were also recruited from the UCSF staff, willing family members of patients in the clinic, and other eligible and willing volunteers. All participants with MS were recruited as part of studies to determine the feasibility [ 18 ] and preliminary efficacy [ 17 ] of the EVO platform as a digital therapeutic to improve processing speed in people with MS. The analysis of this study was based on baseline performance data (ie, before any cognitive intervention) of our feasibility [ 18 ] and efficacy [ 17 ] trials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations